Pure pulmonary stenosis - Chaman Ortíz, José M. (1967)
The invaluable help of the new procedures for cardiology research has allowed us to better study the various cardiac abnormalities . These plays an important role intracardiac catheterization, which allows us to determine data such as blood gases and pressure curves ; the cineangiocardiografía can detect small abnormalities that escape even the intracardiac catheterization and the boom that has nowadays cardiac surgery using cardiopulmonary bypass. Thus we have , reviewing studies in past decades especially in regard to congenital heart disease and pulmonary stenosis including concepts and found Pure percentages have varied. Since Morgagni in 1791 , he described the first case of pulmonary valve stenosis , to Abbot ( 9 cases) , Brock and Campbell ( 18 cases) Abrahams and Wood ( 26 cases ) Kirklin et al. ( 100 cases ) and others, we come to 1961 when Sherf exhaustive study takes the form of this anomaly with the aid of angiocardiography . Therefore we can see that isolated pulmonary stenosis is not of exceptional rarity (63 ) as initially thought . As it has been refined auxiliary diagnostic methods has been demonstrated that it is more frequent ; ranking third or fourth among congenital heart disease . The purpose of this study is to report the study of 22 cases of pulmonary stenosis Pura, who were seen in the cardiology department of the Central Military Hospital between 1960-1964 .